Validation and diagnosis of the design applied to a mixture of biodegradable detergents - Núñez Venegas, Oscar Julio (2025)
The objective of this research work is to validate the design and diagnose the mixture of biodegradable detergents for opinionative sampling as a subset of the population. The mixture of biodegradable detergents is composed of quinoa saponin and adjuvants (sodium carbonate, sodium silicate, sodium tripolyphosphate, and carboxymethylcellulose), and water, creating a 20-row matrix, between 6 pure components, 6 internal mixtures, 6 mixtures excluding one component at a time and 2 centroids, and sampling-dependent variables: Rpta-1, Rpta-2, and Rpta-3. With Minitab 18 software, the angle of repose technique was used, and the variables Rpta-1 and Rpta-3 achieved positive slopes, indicating the quinoa saponin with greater activity. In the first stage, the three simple linear regression equations with opinionated sampling were validated, and only Rpta-3 met the p-value less than 0.05. In the second stage, the entire sample was diagnosed under the assumptions of linearity, homoscedasticity, normality, and independence. Therefore, the article indicates that the linear equation can be achieved, but the diagnostics studied were not obtained; therefore, it does not represent the sample population.